From In Situ to In Vivo: An In Situ Click‐Chemistry‐Derived Carbonic Anhydrase II Imaging Agent for Positron Emission Tomography. Issue 1 (3rd December 2012) - Mocharla, Vani P.; Walsh, Joseph C.; Padgett, Henry C.; Su, Helen; Fueger, Barbara; Weber, Wolfgang A.; Czernin, Johannes; Kolb, Hartmuth C.
<x xml:space="preserve">Abstract</x> CA II makes a good PET: Discovering positron emission tomography (PET) probes with high target affinities is challenging. PET probe discovery using in situ click chemistry uses 19F‐bearing fragments as 18F surrogates. This ensures that the lead hits and PET probes have equivalent chemical or biological characteristics, making PET probe discovery predictable and reliable.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>